THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN ENHANCING CREATIVITY IN PHASE B STUDENTS AT SDN PEKAYON 11 PAGI - Julaeha, Siti (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the effectiveness of Project-Based Learning (PjBL) in enhancing the creativity of Phase B students (Grades III and IV) at SDN Pekayon 11 Pagi. Method: A quasi-experimental design with a mixed-methods approach was employed in this study. Data were collected using creativity observation sheets, project assessment rubrics, and student interviews. Results: The findings revealed that the implementation of PjBL significantly improved various aspects of student creativity, including fluency, flexibility, originality, and elaboration. PjBL facilitated an active, collaborative, and challenging learning environment that encouraged students to engage in divergent and creative thinking while completing tasks. Novelty: This research contributes to the growing body of evidence on the effectiveness of PjBL in enhancing creativity, particularly in Phase B elementary school students. It underscores the potential of PjBL to foster a dynamic learning atmosphere that nurtures creativity and critical thinking in young learners.